Long-Term Monitoring of the Broad-Line Region Properties in a Selected Sample of AGN - Ilić, Dragana; Shapovalova, Alla I.; Popović, Luka Č.; Chavushyan, Vahram; Burenkov, Alexander N.; Kollatschny, Wolfram; Kovačević, Andjelka; Marčeta-Mandić, Sladjana; Rakić, Nemanja; La Mura, Giovanni; Rafanelli, Piero (Frontiers in Astronomy and Space Sciences, 2017)
We present the results of the long-term optical monitoring campaign of active galactic nuclei (AGN) coordinated by the Special Astrophysical Observatory of the Russian Academy of Science. This campaign has produced a remarkable set of optical spectra, since we have monitored for several decades different types of broad-line (type 1) AGN, from a Seyfert 1, double-peaked line, radio loud and radio quiet AGN, to a supermassive binary black hole candidate. Our analysis of the properties of the broad line region (BLR) of these objects is based on the variability of the broad emission lines. We hereby give a comparative review of the variability properties of the broad emission lines and the BLR of seven different type 1 AGNs, emphasizing some important results, such as the variability rate, the BLR geometry, and the presence of the intrinsic Baldwin effect. We are discussing the difference and similarity in the continuum and emission line variability, focusing on what is the impact of our results to the supermassive black hole mass determination from the BLR properties.